Penile calciphylaxis. Issue 1 (6th November 2020) - Bath, Kulwant; Al Jaber, Emad
Abstract: For small lesions, conservative management including local wound care, debridement, and adjustment of renal replacement therapy may suffice. Consulting palliative care is encouraged to help establish goals of care among patient, family, and medical team. Abstract : For small lesions, conservative management including local wound care, debridement, and adjustment of renal replacement therapy may suffice. Consulting palliative care is encouraged to help establish goals of care among patient, family, and medical team.